UJI CEMARAN MIKROBA ANGKA LEMPENG TOTAL (ALT) DAN ANGKA KAPANG KHAMIR (AKK) PADA EKSTRAK ETANOL UMBI LOBAK PUTIH (Raphanus sativus L.) - Kasmal Ilham; Wahyu Yuliana Solikah; Emelda Emelda; Rizal Fauzi (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
White radish (Raphanus sativus L.) is a food plant with promising potential for development as a raw material for traditional medicines and functional foods. The microbiological quality of plant extracts is a critical parameter in ensuring product safety, particularly with regard to microbial contamination. By measuring the Total Plate Count (TPC) and Yeast and Mold Count (YMC), this study sought to assess the microbiological contamination of the ethanol extract of white radish tubers. In order to measure live microorganisms expressed as CFU/g, the experiments were carried out using the pour plate technique on plate count agar (PCA). The findings demonstrated that the ethanol extract's TPC and YMC values were both less than 1 × 10¹ CFU/g. These values are significantly lower than the maximum limits required by BPOM Regulation Number 29/2023, namely ≤10⁵ CFU/g for TPC and ≤10³ CFU/g for YMC. These findings indicate that the extraction and handling processes produced an extract with minimal microbial contamination. Overall, the results demonstrate that the ethanol extract of white radish meets microbiological safety requirements and is suitable for use as a raw material candidate in the development of traditional medicinal products.